A scoping review on the use of traditional medicine and oral health in Africa. - Moréniké Oluwátóyìn Foláyan; Mobolaji Timothy Olagunju; Olunike Rebecca Abodunrin; Omolola Titilayo Alade (PLoS ONE)
Background This review aimed to chart the landscape of literature concerning the precise applications of traditional medicine in managing specific oral diseases and, in doing so, to pinpoint knowledge gaps surrounding the use of traditional medicine for oral disease management in the African context. Methods A systematic search of the literature was conducted on PubMed, Web of Science, Scopus, and CINAHL. The search was conducted from the inception of the database till September 2023. A search of related citations and references was also carried out. Only English language publications were included. A summary of studies that met the inclusion criteria was conducted. Results Of the 584 records identified, 11 were duplicates and 12 studies, published between 2006 and 2021, met the inclusion criteria. The studies were published from eight countries located in the five sub-regions on the continent. All the studies were either experimental designs or ethnobotanical surveys and they all utilized plant-based remedies. The five experimental studies aimed to assess the impact of whole plants or plant extracts on the three microorganisms responsible for dental caries and seven responsible for periodontal diseases. The number of plant species identified by the seven ethnobotanical surveys ranged from 29 to 62 while the number of plan families ranged from 15 to 29. The remedies were either topical applied, use as mouth rinses, gargled, or chewed. The systemic routes of administration identified were inhalation and drinking. The remedies were used for the treatment of hard such as dental caries and tooth sensitivity, to soft tissue lesions such as mouth ulcers, gingival bleeding, and mouth thrush. Other oral disorders managed include halitosis, jaw fracture, and oral cancer. Conclusions Given the increasing prevalence of oral diseases within the region, the shortage of oral healthcare professionals and limited access to financial resources, it becomes imperative to support the generation of empirical evidence to enhance the provision of traditional medicine for oral healthcare in Africa.